2000
DOI: 10.1056/nejm200005043421804
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Function after Hematopoietic Stem-Cell Transplantation for the Treatment of Severe Combined Immunodeficiency

Abstract: The vestigial thymus in infants with severe combined immunodeficiency is functional and can produce enough T cells after bone marrow transplantation to provide normal immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
137
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 24 publications
5
137
3
1
Order By: Relevance
“…This discovery has been used to study T-cell reconstitution following chemotherapy for HIV, 23 ASCT for myeloma, 24 and bone marrow transplantation for severe combined immunodeficiency. 25 In each situation, peripheral blood TREC content predicted subsequent lymphocyte recovery. Furthermore, the presence of TRECs in the blood of adults suggests residual thymic function beyond adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery has been used to study T-cell reconstitution following chemotherapy for HIV, 23 ASCT for myeloma, 24 and bone marrow transplantation for severe combined immunodeficiency. 25 In each situation, peripheral blood TREC content predicted subsequent lymphocyte recovery. Furthermore, the presence of TRECs in the blood of adults suggests residual thymic function beyond adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have suggested a time-dependent loss of function following T-cell-depleted MMRD BMT, associated with progressive lymphopenia, a restricted T-cell repertoire, decreased thymic output as indicated by reduced levels of TCR excision circles and abnormal humoral immunity. 6 A substantial number of SCID patients may present with a significant number of circulating autologous T cells with variable degrees of cell-mediated function. In recent years, patients with mutations in Jak-3, Zap-70, IL-2Ra and CD3 were reported to have autologous T cells and/or residual T-cell function, commonly referred to as T þ CID.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Normal natural killer cell function after BMT might also be elusive. Patel et al 18 have shown decreases in T-cell production and diversity in many patients with SCID several years after haploidentical BMT, suggesting that true stem cells might not be established from the donor. Moreover, some post-BMT patients with SCID continue to experience frequent infections, growth failure, autoimmune disorders, and chronic lung disease.…”
mentioning
confidence: 99%